Termination of Player Contracts with Just Cause in the Light of CAS and FIFA Jurisprudence - Büyükhatipoğlu, Mahmut Can (Sports and Law: Finding a Balance Between the Game and the Rules, 2026)
Legal disputes concerning employment relationships have significantly increased in parallel with the evolution and commercialization of sports. Player contracts establish a complex structure of reciprocal rights and obligations, the violation of which may lead to severe legal and sporting outcomes, including compensation and disciplinary sanctions. The authority to determine the scope of these rights and obligations, as well as the consequences of contractual breaches, primarily derives from the FIFA Regulations on the Status and Transfer of Players and is subsequently shaped through the jurisprudence of the Court of Arbitration for Sport and the FIFA Dispute Resolution Chamber. International disputes are adjudicated before specialized sport-related adjudicatory bodies, whereas domestic disputes may fall under the jurisdiction of national bodies or courts. This article analyses the grounds and consequences of termination with just cause by examining the relevant regulatory provisions and case law, with the aim of contributing to academic literature and providing guidance for legal practice in the development of a consistent framework.